2015
DOI: 10.1155/2015/829718
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effect of Citrate Reduced Gold and Biosynthesized Silver Nanoparticles on α-Amylase Activity

Abstract: Amylase is one of the important digestive enzymes involved in hydrolysis of starch. In this paper, we describe a novel approach to study the interaction of amylase enzyme with gold nanoparticles (AuNPs) and silver nanoparticles (AgNPs) and checked its catalytic function. AuNPs are synthesized using citrate reduction method and AgNPs were synthesized using biological route employing Ficus benghalensis and Ficus religiosa leaf extract as a reducing and stabilizing agent to reduce silver nitrate to silver atoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…This assumption is supported by previous observations demonstrating drastically increased efficiency of enzymes after immobilization on solid surface as compared to their free forms [43]. Indeed, immobilization of amylase on the surface of Ag-NPs increased its activity by 60-90 % [44]. The enzymatic activity of glucose oxidase, cholinesterase, monoamine oxidase, etc.…”
Section: Discussionsupporting
confidence: 74%
“…This assumption is supported by previous observations demonstrating drastically increased efficiency of enzymes after immobilization on solid surface as compared to their free forms [43]. Indeed, immobilization of amylase on the surface of Ag-NPs increased its activity by 60-90 % [44]. The enzymatic activity of glucose oxidase, cholinesterase, monoamine oxidase, etc.…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, some studies underlined the ability of digestive enzymes to bind around NPs. [75][76][77][78][79][80] Besides, bile salts can also interact with the NPs and complete the corona. [41,81] This corona stabilizes the NPs as it was emphasized by the raise of negative zeta-potential.…”
Section: Discussionmentioning
confidence: 99%
“…The immobilization of biomolecules on metal nanoparticles developed and improved several applications including diagnostics, biosensors and drug delivery [11][12][13][14][15][16]. Several studies reported the immobilization of a-amylase with metal nanoparticles such as magnetic Fe 3 O 4 nanoparticles [17], silica nanoparticles [18], amino-functionalized magnetite nanoparticles [19], gold nanoparticles (AuNPs) and silver nanoparticles (AgNPs) [20]. However, using high-intensity ultrasound, in situ generated a-amylase nanoparticles (NPs) were immobilized on polyethylene films [21].…”
Section: Introductionmentioning
confidence: 99%